Preparation method and application of nitrogen-doped carbon intercalation MoS2 (at) MCNTs

By introducing a nitrogen-doped carbon intercalation structure into the molybdenum disulfide/carbon composite material, the problem of poor sodium storage performance in the prior art is solved, higher conductivity and cyclic stability are achieved, and the electrochemical performance of the negative electrode of the sodium ion battery is improved.

CN119637938APending Publication Date: 2025-03-18DEZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411973785.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

There are differences in the sodium storage performance of existing molybdenum disulfide/carbon composite materials, mainly because the carbon layer insertion structure does not contain nitrogen atom doping, resulting in insufficient conductivity and cyclic stability.

Method used

The preparation method of nitrogen-doped carbon intercalation MoS2@MCNTs is adopted to form a carbon intercalation structure containing pyrrole nitrogen through surface activation of multi-wall carbon nanotubes, pyrolysis reaction and high-temperature annealing steps, thereby enhancing the conductivity and stability of molybdenum disulfide.

Benefits of technology

It improves the conductivity and electrochemical properties of MoS2 complex, enhances the diffusion ability and cycling stability of sodium ions, and improves the sodium storage performance of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119637938A_ABST
    Figure CN119637938A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of nitrogen-doped carbon intercalation MoS2 (at) MCNTs, and relates to a preparation method and application of MoS2 (at) MCNTs. The invention aims to solve the problem of poor sodium storage performance of the existing molybdenum disulfide / carbon composite material. The method comprises the following steps: 1, preparing a surface-activated multiwalled carbon nanotube aqueous solution; 2, carrying out pyrolytic reaction; and 3, high-temperature annealing. The preparation method is used for preparing a sodium ion battery negative electrode. The preparation method is used for preparation and application of the nitrogen-doped carbon intercalation MoS2 (at) MCNTs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to MoS 2 @MCNTs preparation method and application. Background Art

[0002] Molybdenum disulfide is the main component of molybdenite. It is a graphene-like layered metal sulfide with abundant reserves and low cost. It has a large theoretical sodium storage capacity (670mAh g -1 However, the low conductivity, easy pulverization during the cycle, and easy dissolution of molybdenum and sulfur components have seriously restricted the development of MoS 2 Electrochemical sodium storage performance of MoS based anode materials. 2 Na-embedded + In the reaction, 2H-MoS 2 First, a phase transition occurs to 1T-MoS 2 , and then decompose to form metal Mo and Na 2 S, and then something similar to S 8 / Na 2 Reaction of S. molybdenum disulfide and carbon nanocomposites can enhance the Na + The diffusion ability in the bulk phase of the composite material and the improvement of the conductivity of the powder can also effectively prevent the dissolution of the S / Mo components. 2 The crystal has a layered structure, with Mo atoms at the center and S atoms at the edge forming a sandwich-like sheet with strong covalent bonds. The S atomic layer is adjacent to the adjacent S atomic layer, and the gap between the sheets is about 0.62nm, connected by weak van der Waals forces. + During the decomposition reaction, the S atom and the adjacent S atom generate Na 2 S nanoparticles, and Mo atoms are more inclined to agglomerate with neighboring Mo atoms to form metal Mo atomic clusters. + Limited by the high reaction energy barrier, the metal Mo atom cluster can only react with the adjacent Na 2 S forms 1T-MoS 2 , some Na that is not in contact with Mo 2 S reacts to form S 8 . S 8 Its sodium ion derivatives have poor conductivity, are easily pulverized and easily dissolved in the electrolyte, affecting the battery performance of the electrode.

[0003] The MoS 2 Most of the composite materials of MoS / carbon are non-intercalated 2 / carbon composite structure. Intercalated MoS 2The composite structure of molybdenum disulfide / carbon is mostly hydrothermal or solvent thermal process or pyrolysis process. In the electrode of intercalation type structure MoS2 based composite material, the carbon intercalation layer is in direct contact with the S sublayer, the single layer or thin layer of MoS2 sheet is in more complete contact with the carbon, and a larger proportion of sulfur atoms are in direct contact with the carbon component. The carbon layer is inserted between MoS2 sheets, which improves the conductivity of MoS2. It is conducive to the diffusion of ions and inhibits the dissolution of components.

[0004] Due to the close contact with the sulfur atoms in molybdenum disulfide, doping nitrogen atoms in carbon materials can improve the electrochemical properties and surface adsorption capacity of electrode materials. Compared with carbon materials not doped with nitrogen, nitrogen-doped carbon materials have more micropores and defects on the surface, which is conducive to the attachment of sulfur components; nitrogen atoms have a strong bonding effect on polysulfide, which can effectively inhibit its dissolution and improve the cycle stability of electrode electrochemical sodium storage. The nitrogen atoms in nitrogen-doped carbon can be divided into three types based on the valence bond structure with carbon atoms: pyrrole-type nitrogen atoms, pyridine-type nitrogen atoms and graphitized nitrogen atoms. Among them, pyrrole-type nitrogen has a certain electrocatalytic activity, which can adjust the diffusion rate of sodium ions and inhibit the dissolution of effective components. Pyrrole-type nitrogen-doped carbon compounds have good application prospects in the fields of catalysis, electronic devices, electrochemical sensor devices and energy storage batteries, and are a new material with great application potential.

[0005] However, the existing carbon layer inserted into the molybdenum disulfide sheet does not contain nitrogen atoms, or the doped nitrogen atoms are pyridine-type nitrogen atoms, resulting in poor sodium storage performance of the molybdenum disulfide / carbon composite material. Summary of the invention

[0006] The present invention aims to solve the problem of poor sodium storage performance of existing molybdenum disulfide / carbon composite materials, and further provide a nitrogen-doped carbon intercalated MoS 2 @MCNTs preparation method and application.

[0007] A nitrogen-doped carbon intercalated MoS 2 The preparation method of @MCNTs is carried out according to the following steps:

[0008] 1. Preparation of surface activated multi-walled carbon nanotube aqueous solution:

[0009] placing multi-walled carbon nanotubes in a nitric acid aqueous solution for heating and reaction, then adjusting the pH value to 7 to obtain a solution after reaction, centrifuging the solution after reaction to collect a solid product, and then dispersing the solid product in deionized water to obtain a surface-activated multi-walled carbon nanotube aqueous solution;

[0010] 2. Pyrolysis reaction:

[0011] In an Ar atmosphere, the surface activated multi-walled carbon nanotube aqueous solution was stirred, then the ionic liquid aqueous solution was added and stirred, and then oleylamine and (NH 4 ) 2 MoS4 Ultrasound, in N 2 Under the condition of atmosphere and temperature of 160°C to 240°C, reflux reaction for 30min to 240min, and finally centrifugation and freeze drying to obtain a freeze-dried product;

[0012] 3. High temperature annealing:

[0013] The freeze-dried product was treated at high temperature in an Ar atmosphere at a temperature of 400°C to 750°C, then naturally cooled to room temperature in an Ar atmosphere, and finally washed and dried to obtain nitrogen-doped carbon intercalated MoS 2 @MCNTs.

[0014] A nitrogen-doped carbon intercalated MoS 2 @Application of MCNTs, which are used to prepare negative electrodes for sodium-ion batteries.

[0015] The beneficial effects of the present invention are:

[0016] MoS of the present invention 2 The composite is loaded on the surface of carbon nanotubes, which can enhance its electrical conductivity and effectively relieve microscopic stress during the charge and discharge process to avoid material pulverization. In the composite structure loaded on the surface of carbon nanotubes, the single or thin layer of molybdenum sulfide sheet is in more complete contact with carbon, and a larger proportion of sulfur atoms are in direct contact with the carbon component. The carbon layer is inserted between the molybdenum disulfide sheets, which improves the electrical conductivity of molybdenum disulfide, facilitates the diffusion of ions and inhibits the dissolution of components. Pyrrolic nitrogen has a certain electrocatalytic activity, which can adjust the diffusion rate of sodium ions and inhibit the dissolution of effective components, further improving the battery performance of the electrode.

[0017] The present invention is used for a nitrogen-doped carbon intercalated MoS 2 @MCNTs preparation method and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Nitrogen-doped carbon intercalated MoS prepared in Example 1 2 @MCNTs SEM and HRTEM images, (a) and (b) are SEM images at different magnifications, (c) and (d) are HRTEM images at different magnifications;

[0019] Figure 2 Nitrogen-doped carbon intercalated MoS prepared in Example 1 2 @XPS spectra of MCNTs, (a) is the high-resolution XPS spectrum of molybdenum, (b) is the high-resolution XPS spectrum of sulfur, (c) is the high-resolution XPS spectrum of carbon, and (d) is the high-resolution XPS spectrum of nitrogen;

[0020] Figure 3 Nitrogen-doped carbon intercalated MoS prepared in Example 1 2 @MCNTs sodium storage cycle stability. DETAILED DESCRIPTION

[0021] Specific embodiment 1: This embodiment is a nitrogen-doped carbon intercalated MoS 2 The preparation method of @MCNTs is carried out according to the following steps:

[0022] 1. Preparation of surface activated multi-walled carbon nanotube aqueous solution:

[0023] placing multi-walled carbon nanotubes in a nitric acid aqueous solution for heating and reaction, then adjusting the pH value to 7 to obtain a solution after reaction, centrifuging the solution after reaction to collect a solid product, and then dispersing the solid product in deionized water to obtain a surface-activated multi-walled carbon nanotube aqueous solution;

[0024] 2. Pyrolysis reaction:

[0025] In an Ar atmosphere, the surface activated multi-walled carbon nanotube aqueous solution was stirred, then the ionic liquid aqueous solution was added and stirred, and then oleylamine and (NH 4 ) 2 MoS 4 Ultrasound, in N 2 Under the condition of atmosphere and temperature of 160°C to 240°C, reflux reaction for 30min to 240min, and finally centrifugation and freeze drying to obtain a freeze-dried product;

[0026] 3. High temperature annealing:

[0027] The freeze-dried product was treated at high temperature in an Ar atmosphere at a temperature of 400°C to 750°C, then naturally cooled to room temperature in an Ar atmosphere, and finally washed and dried to obtain nitrogen-doped carbon intercalated MoS 2 @MCNTs.

[0028] The beneficial effects of this embodiment are:

[0029] In this embodiment, MoS 2 The composite is loaded on the surface of carbon nanotubes, which can enhance its electrical conductivity and effectively relieve microscopic stress during the charge and discharge process to avoid material pulverization. In the composite structure loaded on the surface of carbon nanotubes, the single or thin layer of molybdenum sulfide sheet is in more complete contact with carbon, and a larger proportion of sulfur atoms are in direct contact with the carbon component. The carbon layer is inserted between the molybdenum disulfide sheets, which improves the electrical conductivity of molybdenum disulfide, facilitates the diffusion of ions and inhibits the dissolution of components. Pyrrolic nitrogen has a certain electrocatalytic activity, which can adjust the diffusion rate of sodium ions and inhibit the dissolution of effective components, further improving the battery performance of the electrode.

[0030] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the concentration of the nitric acid aqueous solution in step 1 is 2 mol / L to 4.5 mol / L. The rest is the same as specific embodiment 1.

[0031] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the volume ratio of the mass of the multi-walled carbon nanotubes described in step 1 to the nitric acid aqueous solution is 1 mg: (0.5-2.6) mL. The rest is the same as specific implementation method 1 or 2.

[0032] Specific embodiment 4: This embodiment is different from one of specific embodiments 1 to 3 in that: in step 1, multi-walled carbon nanotubes are placed in a nitric acid aqueous solution, reacted for 10 hours to 12 hours at a temperature of 90°C to 140°C and a stirring speed of 50 r / min to 450 r / min, and then the pH value is adjusted to 7 using a NaOH aqueous solution with a concentration of 0.2 mol / L to 2 mol / L to obtain a solution after reaction, and the solution after reaction is centrifuged for 20 minutes to 60 minutes at a speed of 50 r / min to 450 r / min to collect a solid product, and then the solid product is dispersed in deionized water to obtain a surface-activated multi-walled carbon nanotube aqueous solution with a concentration of 1.0 mg / mL to 12.0 mg / mL. The rest is the same as specific embodiments 1 to 3.

[0033] Specific embodiment 5: This embodiment is different from specific embodiments 1 to 4 in that the solute in the ionic liquid aqueous solution described in step 2 is 1-ethyl-3-methylimidazolium chloride, 1-methyl-3-octylimidazolium chloride, 1-ethyl-3-methylimidazolium bromide, 1-ethyl-3-methylimidazolium dicyanamide, 1-butyl-3-methylimidazolium chloride, 1-benzyl-3-methylimidazolium chloride, 1-(2-hydroxyethyl)-3-methylimidazolium chloride or 1-methyl-3-propylimidazolium chloride. Others are the same as specific embodiments 1 to 4.

[0034] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that: the concentration of the ionic liquid aqueous solution in step 2 is 0.5 mol / L to 4 mol / L; the volume ratio of the surface-activated multi-walled carbon nanotube aqueous solution to the ionic liquid aqueous solution in step 2 is 1:(0.2 to 5.4); the volume ratio of the surface-activated multi-walled carbon nanotube aqueous solution in step 2 to oleylamine is 1:(0.6 to 2); the volume of the surface-activated multi-walled carbon nanotube aqueous solution in step 2 is 1:(NH 4 ) 2 MoS 4 The mass ratio of is 1 mL: (0.2-1.2) mg. The rest is the same as the specific embodiments 1 to 5.

[0035] Specific embodiment 7: This embodiment differs from the specific embodiments 1 to 6 in that: in step 2, the surface activated multi-walled carbon nanotube aqueous solution is stirred for 30 min to 50 min under the conditions of Ar atmosphere and stirring speed of 50 r / min to 450 r / min, and then the ionic liquid aqueous solution is added dropwise under the conditions of Ar atmosphere and stirring speed of 50 r / min to 450 r / min and stirred for 60 min to 450 min, and then oleylamine and (NH 4 ) 2 MoS 4 , and ultrasonically perform the treatment for 15 min to 60 min at a power of 1 kW to 2 kW. Other steps are the same as those in the first to sixth embodiments.

[0036] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that the centrifugal separation and freeze drying described in step two is specifically centrifugal separation at a rotation speed of 3000r / min to 8000r / min for 15min to 60min, and then drying at a temperature of -40°C to -80°C for 12h to 48h. The rest is the same as specific embodiments one to seven.

[0037] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: in step 3, the temperature is raised to 400°C to 750°C at a heating rate of 0.5°C / min to 3°C / min under Ar atmosphere, and then the freeze-dried product is subjected to high temperature treatment for 1h to 12h under Ar atmosphere and temperature of 400°C to 750°C. The rest is the same as specific embodiments 1 to 8.

[0038] Specific embodiment 10: This embodiment is a nitrogen-doped carbon intercalated MoS 2 @Application of MCNTs, which are used to prepare negative electrodes for sodium-ion batteries.

[0039] The following examples are used to verify the beneficial effects of the present invention:

[0040] Embodiment 1:

[0041] A nitrogen-doped carbon intercalated MoS 2 The preparation method of @MCNTs is carried out according to the following steps:

[0042] 1. Preparation of surface activated multi-walled carbon nanotube aqueous solution:

[0043] The multi-walled carbon nanotubes were placed in a nitric acid aqueous solution, reacted for 11 hours at a temperature of 100° C. and a stirring speed of 120 r / min, and then the pH value was adjusted to 7 with a 1 mol / L NaOH aqueous solution to obtain a solution after the reaction, and the solution after the reaction was centrifuged for 40 minutes at a speed of 120 r / min to collect a solid product, and then the solid product was dispersed in deionized water to obtain a surface-activated multi-walled carbon nanotube aqueous solution with a concentration of 4.0 mg / mL;

[0044] The concentration of the nitric acid aqueous solution is 3 mol / L; the mass ratio of the multi-walled carbon nanotubes to the nitric acid aqueous solution is 1 mg:1.5 mL;

[0045] 2. Pyrolysis reaction:

[0046] Under the conditions of Ar atmosphere and stirring speed of 120r / min, the surface activated multi-walled carbon nanotube aqueous solution was stirred for 30min, then under the conditions of Ar atmosphere and stirring speed of 120r / min, the ionic liquid aqueous solution was dropped into it and stirred for 120min, and then oleylamine and (NH 4 ) 2 MoS 4 , ultrasonically heated for 40 min at a power of 1 kW, and heated at N 2 Under the conditions of an atmosphere and a temperature of 170°C, reflux reaction was carried out for 150 minutes, centrifuged at a speed of 5000 r / min for 40 minutes, and then dried at a temperature of -80°C for 18 hours to obtain a freeze-dried product;

[0047] The concentration of the ionic liquid aqueous solution is 0.5 mol / L; the volume ratio of the surface activated multi-walled carbon nanotube aqueous solution to the ionic liquid aqueous solution is 1:2; the volume ratio of the surface activated multi-walled carbon nanotube aqueous solution to oleylamine is 1:1; the volume of the surface activated multi-walled carbon nanotube aqueous solution is 1:1. 4 ) 2 MoS 4 The mass ratio is 1mL:1mg;

[0048] The solute in the ionic liquid solution is 1-ethyl-3-methylimidazolium chloride;

[0049] 3. High temperature annealing:

[0050] In an Ar atmosphere, the temperature was raised to 600°C at a rate of 1.0°C / min, and then the freeze-dried product was treated at high temperature for 5 h in an Ar atmosphere at 600°C, and then naturally cooled to room temperature in an Ar atmosphere, and finally washed and dried to obtain nitrogen-doped carbon intercalated MoS 2@MCNTs.

[0051] Figure 1 Nitrogen-doped carbon intercalated MoS prepared in Example 1 2 SEM and HRTEM images of @MCNTs. (a) and (b) are SEM images at different magnifications, and (c) and (d) are HRTEM images at different magnifications. It can be seen from the figure that MoS 2 The composite is loaded on the surface of carbon nanotubes, and the composite layer is rich in a single layer or thin layer of molybdenum disulfide sheet structure. The interlayer spacing of molybdenum disulfide sheets is 0.64nm. When the interlayer spacing of molybdenum disulfide sheets is greater than 0.98nm, it is a carbon intercalation material embedded in the interlayer of molybdenum disulfide.

[0052] Figure 2 Nitrogen-doped carbon intercalated MoS prepared in Example 1 2 @MCNTs XPS spectrum, (a) is the high-resolution XPS spectrum of molybdenum, (b) is the high-resolution XPS spectrum of sulfur, (c) is the high-resolution XPS spectrum of carbon, and (d) is the high-resolution XPS spectrum of nitrogen. It can be seen from the figure that the composite material is composed of four elements: carbon, nitrogen, molybdenum and sulfur, among which the nitrogen element is mainly composed of pyrrolic nitrogen.

[0053] Nitrogen-doped carbon intercalated MoS prepared in Example 1 2 @MCNTs was used as the electrode material, sodium metal sheet as the counter electrode, glass cellulose membrane (whatman D) as the separator, EC:DEC:FEC with a volume ratio of 1:1:0.05 as the electrolyte. The electrodes were assembled and packaged in a 2016 button battery case, and then charge and discharge tests were carried out after packaging. Figure 3 Nitrogen-doped carbon intercalated MoS prepared in Example 1 2 @MCNTs sodium storage cycle stability. As can be seen from the figure, MoS 2 The base electrode discharge capacity is 524.4 mAhg -1 After 200 cycles, the capacity remained at 481.3 mAh g -1 , the cycle efficiency is higher than 99.5%.

Claims

1. A method for preparing nitrogen-doped carbon intercalated MoS2@MCNTs, characterized in that It is carried out in the following steps:

1. Preparation of surface activated multi-walled carbon nanotube aqueous solution: placing multi-walled carbon nanotubes in a nitric acid aqueous solution for heating and reaction, then adjusting the pH value to 7 to obtain a solution after reaction, centrifuging the solution after reaction to collect a solid product, and then dispersing the solid product in deionized water to obtain a surface-activated multi-walled carbon nanotube aqueous solution; 2. Pyrolysis reaction: In an Ar atmosphere, a surface activated multi-walled carbon nanotube aqueous solution is stirred, an ionic liquid aqueous solution is then dropped into the solution and stirred, and then oleylamine and (NH4)2MoS4 are dropped into the solution and ultrasonically reacted, and a reflux reaction is performed for 30 min to 240 min in an N2 atmosphere at a temperature of 160°C to 240°C, and finally centrifugation and freeze-drying are performed to obtain a freeze-dried product; 3. High temperature annealing: The freeze-dried product was treated at high temperature in an Ar atmosphere at a temperature of 400°C to 750°C, then naturally cooled to room temperature in an Ar atmosphere, and finally washed and dried to obtain nitrogen-doped carbon intercalated MoS2@MCNTs.

2. The method for preparing nitrogen-doped carbon intercalated MoS2@MCNTs according to claim 1, characterized in that The concentration of the nitric acid aqueous solution described in step 1 is 2 mol / L to 4.5 mol / L.

3. The method for preparing nitrogen-doped carbon intercalated MoS2@MCNTs according to claim 1, characterized in that The volume ratio of the mass of the multi-walled carbon nanotubes described in step 1 to the nitric acid aqueous solution is 1 mg: (0.5-2.6) mL.

4. The method for preparing nitrogen-doped carbon intercalated MoS2@MCNTs according to claim 1, characterized in that In step 1, the multi-walled carbon nanotubes are placed in a nitric acid aqueous solution, reacted for 10 hours to 12 hours at a temperature of 90° C. to 140° C. and a stirring speed of 50 r / min to 450 r / min, and then the pH value is adjusted to 7 using a NaOH aqueous solution with a concentration of 0.2 mol / L to 2 mol / L to obtain a reacted solution, and the reacted solution is centrifuged for 20 minutes to 60 minutes at a rotation speed of 50 r / min to 450 r / min to collect a solid product, and then the solid product is dispersed in deionized water to obtain a surface-activated multi-walled carbon nanotube aqueous solution with a concentration of 1.0 mg / mL to 12.0 mg / mL.

5. The method for preparing nitrogen-doped carbon intercalated MoS2@MCNTs according to claim 1, characterized in that The solute in the ionic liquid aqueous solution described in step 2 is 1-ethyl-3-methylimidazolium chloride, 1-methyl-3-octylimidazolium chloride, 1-ethyl-3-methylimidazolium bromide, 1-ethyl-3-methylimidazolium dicyanamide, 1-butyl-3-methylimidazolium chloride, 1-benzyl-3-methylimidazolium chloride, 1-(2-hydroxyethyl)-3-methylimidazolium chloride or 1-methyl-3-propylimidazolium chloride.

6. The method for preparing nitrogen-doped carbon intercalated MoS2@MCNTs according to claim 1, characterized in that The concentration of the ionic liquid aqueous solution described in step 2 is 0.5 mol / L~4 mol / L; the volume ratio of the surface-activated multi-walled carbon nanotube aqueous solution described in step 2 to the ionic liquid aqueous solution is 1:(0.2~5.4); the volume ratio of the surface-activated multi-walled carbon nanotube aqueous solution described in step 2 to oleylamine is 1:(0.6~2); the mass ratio of the volume of the surface-activated multi-walled carbon nanotube aqueous solution described in step 2 to (NH4)2MoS4 is 1mL:(0.2~1.2)mg.

7. The method for preparing nitrogen-doped carbon intercalated MoS2@MCNTs according to claim 1, characterized in that In step 2, the surface-activated multi-walled carbon nanotube aqueous solution is stirred for 30 to 50 minutes in an Ar atmosphere at a stirring speed of 50 to 450 r / min, and then the ionic liquid aqueous solution is dropped into it and stirred for 60 to 450 minutes in an Ar atmosphere at a stirring speed of 50 to 450 r / min, and then oleylamine and (NH4)2MoS4 are dropped into it, and ultrasonication is performed for 15 to 60 minutes at a power of 1 kW to 2 kW.

8. The method for preparing nitrogen-doped carbon intercalated MoS2@MCNTs according to claim 1, characterized in that The centrifugal separation and freeze-drying described in step 2 specifically comprises centrifugal separation at a rotation speed of 3000r / min to 8000r / min for 15min to 60min, and then drying at a temperature of -40°C to -80°C for 12h to 48h.

9. The method for preparing nitrogen-doped carbon intercalated MoS2@MCNTs according to claim 1, characterized in that In step three, under Ar atmosphere, the temperature is increased at a rate of 0.5°C / min to 3°C / min to a temperature of 400°C to 750°C, and then the freeze-dried product is treated at high temperature for 1h to 12h under Ar atmosphere and a temperature of 400°C to 750°C.

10. The use of nitrogen-doped carbon intercalated MoS2@MCNTs prepared as claimed in claim 1, characterized in that It is used to prepare the negative electrode of sodium-ion batteries.